Influence of the Use of an Additional Oxidant (Chlorine Dioxide) in Water Treatment on Swimming Pool Water Quality - Agnieszka Włodyka-Bergier; Tomasz Bergier (Energies, 2022)
This article presents the results of experiments on the effect of chlorine dioxide, applied as an additional oxidant, on swimming pool water quality. Three doses of chlorine dioxide were applied: 22, 44 and 66 mg/m3. At each research stage, prior to the actual experiment, in which the oxidant was dosed, the background was tested, i.e., water samples were taken from a conventional treatment system (without chlorine dioxide). The experiments showed that chlorine dioxide effectively removes organic compounds and their chlorine derivatives. For the highest dose of ClO2, CODMn decreased by almost 88% and chloroform concentration by 75%. Chlorine dioxide also effectively supports water disinfection. At the highest dose, the number of mesophilic bacteria decreased by 60% and the number of psychrophiles by 94%. However, after the dosing of this oxidant had been discontinued, a deterioration of the microbiological water quality and the secondary growth of microorganisms were observed. Chlorine dioxide also caused an increase in conductivity and the concentration of inorganic compounds (nitrates, total chlorates and chlorites). The effect of this agent on the combined chlorine concentration was not observed. The reported experiments have shown that this measure is not unequivocally beneficial in terms of improving swimming pool water quality.